Interactions between Verticillium dahliae and cotton: pathogenic mechanism and cotton resistance mechanism to Verticillium wilt - Zhu, Yutao; Zhao, Mei; Li, Taotao; Wang, Lianzhe; Liao, Chunli; Liu, Dongxiao; Zhang, Huamin; Zhao, Yanpeng; Liu, Lisen; Ge, Xiaoyang; Li, Bingbing (Frontiers in Plant Science, 2023)
Cotton is widely grown in many countries around the world due to the huge economic value of the total natural fiber. Verticillium wilt, caused by the soil-borne pathogen Verticillium dahliae, is the most devastating disease that led to extensive yield losses and fiber quality reduction in cotton crops. Developing resistant cotton varieties through genetic engineering is an effective, economical, and durable strategy to control Verticillium wilt. However, there are few resistance gene resources in the currently planted cotton varieties, which has brought great challenges and difficulties for breeding through genetic engineering. Further revealing the molecular mechanism between V. dahliae and cotton interaction is crucial to discovering genes related to disease resistance. In this review, we elaborated on the pathogenic mechanism of V. dahliae and the resistance mechanism of cotton to Verticillium wilt. V. dahliae has evolved complex mechanisms to achieve pathogenicity in cotton, mainly including five aspects: (1) germination and growth of microsclerotia; (2) infection and successful colonization; (3) adaptation to the nutrient-deficient environment and competition of nutrients; (4) suppression and manipulation of cotton immune responses; (5) rapid reproduction and secretion of toxins. Cotton has evolved multiple physiological and biochemical responses to cope with V. dahliae infection, including modification of tissue structures, accumulation of antifungal substances, homeostasis of reactive oxygen species (ROS), induction of Ca2+ signaling, the mitogen-activated protein kinase (MAPK) cascades, hormone signaling, and PAMPs/effectors-triggered immune response (PTI/ETI). This review will provide an important reference for the breeding of new cotton germplasm resistant to Verticillium wilt through genetic engineering.